Circadian rhythms and circadian clock gene homologs of complex alga Chromera velia - Richtová, Jitka; Bazalová, Olga; Horák, Aleš; Tomčala, Aleš; Gonepogu, Vijaya Geetha; Oborník, Miroslav; Doležel, David (Frontiers in Plant Science, 2023)
Most organisms on Earth are affected by periodic changes in their environment. The circadian clock is an endogenous device that synchronizes behavior, physiology, or biochemical processes to an approximately 24-hour cycle, allowing organisms to anticipate the periodic changes of day and night.Although circadian clocks are widespread in organisms, the actual molecular components differ remarkably among the clocks of plants, animals, fungi, and prokaryotes. We examined the presence of daily activity in Chromera velia, the closest known photosynthetic relative of apicomplexan parasites. C. velia has a motile stagezoospores, the formation of which has been described as associated with the light part of the day. Here we showed the effects on the periodic release of the 2 zoospores under different light conditions. Further, we investigated the effects of the spectral composition to zoosporogenesis and identified the blue light spectra as the essential compound. We also developed a new and effective method for zoospore separation from the culture and estimated the average speed and lifespan of the C. velia zoospores. Our genomic search identified six cryptochrome-like genes, two genes possibly related to Arabidopsis thaliana CCA/LHY, whereas no homolog of an animal, cyanobacterial, or fungal circadian clock gene was found. Our results suggest that C. velia has a functional circadian clock, probably based mainly on an as yet undefined mechanism.